2012
DOI: 10.1503/cmaj.111719
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress as a risk factor for death from cerebrovascular disease

Abstract: Little is known about psychological risk factors in cerebrovascular disease. We examined the association between psychological distress and risk of death due to cerebrovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 27 publications
(42 reference statements)
0
28
0
1
Order By: Relevance
“…Evidence from prospective cohort studies in humans that has emerged over the last several decades consistently demonstrates an association between various psychosocial risk factors and future risk of cardiovascular disease (CVD) in both initially healthy samples and cardiac patients (1)(2)(3)(4), with effect sizes that are comparable to conventional risk factors such as hypertension, obesity and smoking (5).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from prospective cohort studies in humans that has emerged over the last several decades consistently demonstrates an association between various psychosocial risk factors and future risk of cardiovascular disease (CVD) in both initially healthy samples and cardiac patients (1)(2)(3)(4), with effect sizes that are comparable to conventional risk factors such as hypertension, obesity and smoking (5).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated that psychological conditions can influence a person's risk of cardiovascular diseases. 24,25 Hamer et al documented that psychological distress is connected with increased mortality from cerebrovascular disease. 25 One of the possible explanations for the lagging effect of margin trading may be due to regulation.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Hamer et al documented that psychological distress is connected with increased mortality from cerebrovascular disease. 25 One of the possible explanations for the lagging effect of margin trading may be due to regulation. In Taiwan, investors who receive a margin call do not need to sell off their stocks or add more cash to their margin account immediately; rather, they are forced to make this decision two business days after receiving the margin call.…”
Section: Discussionmentioning
confidence: 99%
“…I n a related CMAJ article, Hamer and colleagues 1 report results from the Health Survey for England showing an association between baseline psychological distress and subsequent increased risk of death due to cerebrovascular disease. Their results are in concordance with findings from previous observational studies and highlight the connection between psy chological and cardiovascular health.…”
mentioning
confidence: 99%
“…Cognitive behavioural therapy may provide additional benefits in conjunction with standard treatment. 10 In light of the findings by Hamer and colleagues, 1 we need further studies to test whether treatment aimed at alleviating psychological distress (e.g., pharmacological medications, cognitive behavioural therapy and lifestyle management) will reduce cardiovascular risk. A well-designed clinical trial may answer the question, but it will require a study of large sample size and sufficient long-term follow-up to test change in outcomes related to cardiovascular disease.…”
mentioning
confidence: 99%